Old Jewish Folk Music : the Collections and Writings of Moshe Beregovski - Slobin, Mark (Publications of the American Folklore Society ;, 2016)
Here presented for the first time in English are Beregovski's surviving essays, plus his anthologies containing hundreds of folk songs with full Yiddish and English texts.